Black America: Multimodal Discourse Analysis of Childish Gambino’s “This is America” - Mona Audryn Margaretha; Yasmine Anabel Panjaitan (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2020)
A song can manifest itself as a critical instrument in the vast socio-political atmosphere. Often times a song conceals its real meaning within layers of linguistic elements and through visual communication. Upon the release of Childish Gambino’s This is America (2018), the music video has been assumed widely assumed to contain semiotic elements that criticize the injustice politics of race in America. To dig deeper into this assertion, we use Machin’s Lyrics Analysis (2010) and Kress and van Leeuwen’s Visual Grammar approach (2006) to analyze the illustrated semiotic elements. Both frameworks are two Multimodal Discourse Analysis approaches that explore interdisciplinary analysis in the discourse-oriented research. This article finds that Gambino does question the practice of black discrimination through gun and police violence in present America by utilizing distant words and excessive gestures in his visual communication as a diversion. They are purposefully placed to gain a profound observation from the audience, and thus able to spark a conversation regarding the issue in a greater scale. Furthermore, it is found that This is America applies comical aspects in the visual elements as a layering device. Through humorous semiotic elements, Gambino is discovered to highlight the commodification of black art in his music video.